A Randomized Crossover Trial of Conventional vs Virtual Chromoendoscopy for Colitis Surveillance: Dysplasia Detection, Feasibility, and Patient Acceptability (CONVINCE). Issue 6 (20th December 2018) - Gulati, Shraddha; Dubois, Patrick; Carter, Ben; Cornelius, Victoria; Martyn, Meredith; Emmanuel, Andrew; Haji, Amyn; Hayee, Bu'Hussain
Abstract: Background: Chromoendoscopy (CE) is the recommended surveillance technique for colitis, but uptake has been limited and the literature provides scant information on patient experience (PE); imperative to adherence to surveillance programmes. Virtual CE (VCE) by Fujinon Intelligent Colour Enhancement digitally reconstructs mucosal images in real time, without the technical challenges of CE. We performed a multifaceted randomized crossover trial (RCT) to evaluate study feasibility and obtain preliminary comparative procedural and PE data. Methods: Patients were randomized to undergo either CE with indigo carmine or VCE as the first procedure. After 3–8 weeks, participants underwent colonoscopy with the second technique. Patient recruitment/retention, missed dysplasia, prediction of dysplasia, and contamination (memory/sampling of the first procedure) were recorded. PE was assessed by validated questionnaires, and pain was assessed using a visual analog scale (mm). Results: Sixty patients were recruited, and 48 patients (first procedure: 23 VCE, 25 CE) completed the trial (retention 80%) with no episodes of contamination. Eleven dysplastic lesions were detected in n = 7/48 (14.5%). VCE missed 1 lesion, and CE missed 2 lesions in n = 2 (data of VCE vs CE, respectively, for dysplasia diagnostic accuracy: 93.94% [85.2%–98.32%] vs 76.9% [66.9%–98.2%]; examination time [minutes]: 14 +/- 4 vs 20 +/- 7 (95% confidence interval, 3.5 to 8; P < 0.001); pain (mm): 27.4 +/- 17.5 vs 34.7 +/- 18; patient preference: 67% [n = 31] vs 33% [n = 15] in n = 46; P < 0.001). Conclusions: This is the first RCT to include validated PE in a colitis surveillance program. VCE is safe, technically easier, quicker, and more comfortable test, with dysplasia detection at least as good as that of CE, overcoming many barriers to the wider adoption of CE. This trial may serve as a successful foundation for a a multicenter trial to confirm the value of VCE for colitis surveillance.